Overexpression of Salmonella enterica serovar Typhi recA gene confers fluoroquinolone resistance in Escherichia coli DH5α - Yassien,M.A.M. (2015)
A spontaneous fluoroquinolone-resistant mutant (STM1) was isolated from its parent Salmonella enterica serovar Typhi (S. Typhi) clinical isolate. Unlike its parent isolate, this mutant has selective resistance to fluoroquinolones without any change in its sensitivity to various other antibiotics. DNA gyrase assays revealed that the fluoroquinolone resistance phenotype of the STM1 mutant did not result from alteration of the fluoroquinolone sensitivity of the DNA gyrase isolated from it. To study the mechanism of fluoroquinolone resistance, a genomic library from the STM1 mutant was constructed in Escherichia coli DH5α and two recombinant plasmids were obtained. Only one of these plasmids (STM1-A) conferred the selective fluoroquinolone resistance phenotype to E. coli DH5α. The chromosomal insert from STM1-A, digested with EcoRI and HindIII restriction endonucleases, produced two DNA fragments and these were cloned separately into pUC19 thereby generating two new plasmids, STM1-A1 and STM1-A2. Only STM1-A1 conferred the selective fluoroquinolone resistance phenotype to E. coli DH5α. Sequence and subcloning analyses of STM1-A1 showed the presence of an intact RecA open reading frame. Unlike that of the wild-type E. coli DH5α, protein analysis of a crude STM1-A1 extract showed overexpression of a 40 kDa protein. Western blotting confirmed the 40 kDa protein band to be RecA. When a RecA PCR product was cloned into pGEM-T and introduced into E. coli DH5α, the STM1-A11 subclone retained fluoroquinolone resistance. These results suggest that overexpression of RecA causes selective fluoroquinolone resistance in E. coli DH5α.